A Case of Infantil Herpes Zoster - Çiçek, Demet (Fırat University, 2007)
18-month infant patient applied to our polyclinic with the complaint of a wound on the back. It was determined that the patient had varicella due to anamnesis six months ago. As a result of the dermatological examination, it was determined that there were vesicules and hemorrhagic cruts at some points, which formed groups on the erythematic ground beginning on the middle line and including right scapular region and advancing towards the axiller region and the frontal surface of the body. In the laboratory examinations, in the tzanck smear test carried out on the vesicule liquid of the patient, multinuclear huge cells were determined and VZV IgG was determined as positive. Based on the clinical, tzanck smear and serological findings, the patient was diagnosed with Herpes zoster and systemic aciclovir treatment was commenced with dose of 20 mg/kg/day. Beginning from the third day of the treatment, improvement was determined in the lesions of the patient. ©2007, Firat University, Medical Faculty

18 aylık bebek hasta sırtında yara şikayeti ile polikliniğimize getirildi. Hastanın anamneziden altı ay önce suçiçeği geçirdiği öğrenildi. Yapılan dermatolojik muayenede sırtta orta hattan başlayıp sağ skapular bölgeyi de içeren, axiller bölge ve gövde ön yüzüne ilerleyen eritemli zemin üzerinde gruplar oluşturmuş veziküller ve yer yer hemorajik krutlar mevcuttu. Laboratuar incelemelerinde, hastanın vezikül sıvısından yapılan tzanck smear testinde multinukleer dev hücrelere rastlandı ve VZV IgG pozitif olarak saptandı. Klinik, tzanck smear ve serolojik bulgular doğrultusunda Herpes zoster tanısı konulan hastaya 20 mg/kg/gün dozunda sistemik asiklovir tedavisi başlandı. Tedavinin üçüncü gününden itibaren hastanın lezyonlarında iyilesme tespit edildi. ©2007, Fırat Üniversitesi, Tıp Fakültesi
İnfantil Dönemde Bir Herpes Zoster Olgusu